HIGHER EDUCATION GOVERNANCE OF MUSLIM MINORITY: EFFORTS TO BE PART OF NATION’S DEVELOPMENT - Ismail Suardi Wekke (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2018)
Abstract The findings of this study may contribute to the government’s efforts to tackle the terrorist movement in Indonesia. Education, until today, is believed to be one of the methods to conduct knowledge transformation. However, in the implementation of education, accessibility sometimes becomes one of the obstacles. Hence, this paper described several matters concerning the extension of access to education. This matter required a political policy concerning the availability of educational facilities. Set in West Papua Province, this study described higher education strengthening individual capacity. When an individual is capable and being empowered, it means that not only his/her family who enjoy that ability, but also the society and the nation will enjoy the advance and competitiveness of human resource excellence. This qualitative study also showed through data collection in descriptive way from observation during how limitations can be sources of strength. So the limitations need not be regarded as obstacles, but should even be opportunities to do innovations. The study also concluded how an unorganized higher education can have an impact on the economy that will hamper the journey to seize the opportunity to know. Finally, with the reconstruction of various resources, universities can remain the best means of providing energy to serve civilization. Keywords: Higher Education, Access, and Resources Abstrak Temuan penelitian ini berkontribusi terhadap upaya pemerintah dalam menanggulangi gerakan teroris di Indonesia. Pendidikan hingga hari ini diyakini sebagai sebuah metode untuk melakukan transformasi pengetahuan. Namun demikian, pada tataran implementasi, aksestabilitas pendidikan merupakan sebuah permasalahan tersendiri. Untuk itu, tulisan ini memberikan beberapa hal terkait dengan perluasan aksestabilitas pendidikan. Upaya perluasan harus ditopang oleh kebijakan politis terkait dengan ketersediaan fasilitas pendidikan. Studi yang dilakukan di Provinsi Papua Barat mendeskripsikan perguruan tinggi yang tengah memperkuat kapasitas individu civitas akademikanya. Manakala individu terberdayakan, tidak hanya keluarganya, tetapi masyarakat dan negaranya akan merasakan dampak positifnya. Penelitian kualitatif ini menggunakan data deskriptif dan observasi, penelitian juga menunjukkan bahwa keterbatasan aksestabilitas pendidikan adalah sumber kekuatan. Keterbatasan tersebut tidak pantas dipandang penghalang, melainkan sebagai tantangan untuk melakukan inovasi. Studi ini juga menyimpulkan bahwa sebuah perguruan tinggi yang kurang terorganisir memberikan dampak ekonomi yang menghalangi kesempatan untuk mendapatkan pengetahuan. Akhirnya, melalui rekonstruksi terhadap ragam sumber daya yang tersedia, perguruan tinggi diyakini tetap merupakan wahana penyedia energi positif bagi perkembangan peradaban. Kata kunci: perguruan tinggi, akses, dan sumber daya